1990
DOI: 10.2307/3898931
|View full text |Cite
|
Sign up to set email alerts
|

Phenological Patterns and Adaptations in an Artemisia/Agropyron Plant Community

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
(21 reference statements)
2
7
0
Order By: Relevance
“…In this manner, regrowth is allowed to occur, continuing the main growing season. It is likely that, as found by Pitt and Wikeem [1990], soil moisture is a strong control of growth in many grasslands. For this research, we chose to employ simple, commonly available meteorological data to drive the models.…”
Section: Model Developmentmentioning
confidence: 82%
“…In this manner, regrowth is allowed to occur, continuing the main growing season. It is likely that, as found by Pitt and Wikeem [1990], soil moisture is a strong control of growth in many grasslands. For this research, we chose to employ simple, commonly available meteorological data to drive the models.…”
Section: Model Developmentmentioning
confidence: 82%
“…For example, Knapp (1984) found that the reproductive effort could be significantly diminished during drought. Pitt and Wikeem (1990) also found that soil moisture was a strong controlling factor of plant growth in middle latitude steppe. But many phenological models or phenological modules in a dynamic global vegetation model (DGVM) for grassland ecosystems were found to be solely driven by temperature (Verseghy et al 1993;White et al 1997;Foley et al 1996;Sitch et al 2003).…”
Section: Introductionmentioning
confidence: 86%
“…However, very little work has been reported so far on plant phenology in grassland ecosystems, where phenology is controlled by both soil moisture and temperature in one particular climatic regime (Dickinson and Dodd 1976;Pitt and Wikeem 1990;Stewart and Dwyer 1994). In some savanna and desert shrub grassland ecosystems, which are totally driven by water, plant growth is largely controlled by precipitation and drought stress (Burk 1982;Kemp 1983;Sharifi et al 1988;Xu and Baldocchi 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Flowering or pollination occurs during late summer to mid-fall with fruit development commencing almost simultaneously with flowering and achenes (dry single-seeded fruit) ) maturing during midfall to midwinter (DePuit and Caldwell1973; Everett and others 1980;Pitt and Wikeem 1990;Sauer and Uresk 1976). Thus, reproductive growth occurs when water supplies and temperatures are not particularly favorable; in fact, during this period, big sagebrush plants have started shedding ephemeral leaves from vegetative shoots and neighboring plant species are largely dormant (Miller and others 1983).…”
Section: Seed Production ________________ Reproductive Growthmentioning
confidence: 99%
“…The small mature achenes or seeds are wind dispersed from midfall to midwinter; however, big sagebrush achenes lack special structures that would aid in long distance dispersal, 100 feet being maximum (Everett and others 1980;Pendleton and others 1989;Pitt and Wikeem 1990;Sauer and Uresk 1976;Welch and others 1990;. Most achenes are dispersed within 3 or 4 feet from the mother plant, and achenes are not dispersed evenly but are heavily influenced by wind direction.…”
Section: Seed Dispersalmentioning
confidence: 99%